A modified polyvinylidene fluoride membrane, and a preparation method and application thereof

CN122912701APending Publication Date: 2026-10-16SHANGHAI INST OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611207198.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,该方案中的UiO-66-NH2颗粒主要依靠抽滤沉积和PEI的物理粘附作用负载于膜表面,颗粒与膜基底之间的结合力较弱,在高剪切力或反冲洗条件下易脱落;同时该方案中的改性膜不具备光催化自清洁能力,污染后的通量恢复仍需依赖外部化学清洗

Benefits of technology

(1)本发明创新性地将硫化铋修饰的NH2-UIO-66颗粒引入经PAA改性后的PVDF膜上,成功制得了集抗生素分离和光催化表面自清洁于一体的改性聚偏二氟乙烯膜。本发明制得的改性PVDF膜不仅具有优秀的抗生素截留性能,还有良好的光催化自清洁新能,水通量可达50 L·h-1·m-2·bar-1,单次环丙沙星截留率>95 %,为在模拟太阳光照射下,水通量恢复率>60 %,在抗生素废水处理方面具有重要的应用潜力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912701A_ABST
    Figure CN122912701A_ABST
Patent Text Reader

Abstract

The application relates to a modified polyvinylidene fluoride membrane and a preparation method and application thereof, and belongs to the field of membrane separation technology. The preparation method comprises the following steps: preparing bismuth sulfide particles; mixing the bismuth sulfide particles with a zirconium source, 2-amino terephthalic acid and a regulator, and preparing bismuth sulfide modified NH2-UIO-66 particles through a hydrothermal reaction; pouring a mixed solution containing acrylic acid, ethylene glycol and an initiator onto the surface of a polyvinylidene fluoride membrane treated with an alkali solution, and heating to obtain a polyacrylic acid grafted polyvinylidene fluoride membrane; transferring a bismuth sulfide modified NH2-UIO-66 particle dispersion liquid to the surface of the polyacrylic acid grafted polyvinylidene fluoride membrane, and finally obtaining a modified polyvinylidene fluoride membrane. Compared with the prior art, the modified PVDF membrane has good water flux, excellent antibiotic interception effect and good surface self-cleaning capacity, the flux recovery rate is high and stable, and the modified PVDF membrane has potential application value in antibiotic wastewater treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of membrane separation technology, and in particular to a modified polyvinylidene fluoride membrane, its preparation method, and its application. Background Technology

[0002] Antibiotic wastewater is a significant area of ​​industrial and domestic wastewater treatment. With industrial development, the discharge of wastewater containing high concentrations of antibiotics is increasing and entering the natural environment, threatening ecosystem stability, food security, and human health. Antibiotics in this type of wastewater are persistent, bioaccumulative, and can induce the spread of resistance genes, posing a serious threat to the aquatic environment and human health.

[0003] Among various wastewater treatment technologies, membrane separation is widely used due to its high efficiency and ease of operation. Polyvinylidene fluoride (PVDF) membranes are synthetic high-performance fibers. Their excellent chemical stability ensures long-term stable operation in complex industrial wastewater environments, and their good mechanical properties ensure the integrity of the membrane structure under high-pressure operating conditions, providing an ideal platform for pollutant separation. However, traditional PVDF membranes mainly rely on physical sieving, which can easily lead to problems such as membrane pore clogging, decreased permeability, and limited removal efficiency in practical applications, thus restricting their long-term operational stability and potential for resource recovery and reuse.

[0004] CN112090300A discloses a hydrophilic zirconium-based MOF-doped PVDF membrane. UiO-66-NH2 nanoparticles are modified with 1,3-propanesulfonic acid lactone to obtain UiO-66-NH2-SO3H nanoparticles, which are then hybridized with PVDF. The hydrophilic zirconium-based MOF-doped PVDF membrane is prepared using an immersion phase inversion method, improving the membrane's stability and hydrophilicity. However, this method only physically blends MOF particles into the PVDF matrix, resulting in a lack of stable bonding between the MOF particles and the polymer substrate. Under long-term use or high-pressure operating conditions, particle loss remains a risk. Furthermore, the modified membrane lacks visible light response, failing to achieve in-situ degradation of trapped pollutants, and the membrane fouling problem is not fundamentally alleviated.

[0005] CN115155335A discloses a MOF membrane of PVDF modified with FPEOAAA / UiO-66-NH2 / PEI. This method involves depositing UiO-66-NH2 and polyethyleneimine onto the surface of a polyvinylidene fluoride (PVDF) membrane, and then grafting FPEOAA onto the surface to form the FPEOAA / UiO-66-NH2 / PEI modified PVDF MOF membrane, thereby improving the membrane's stability and hydrophilic-oleophobic properties. However, in this method, the UiO-66-NH2 particles are mainly loaded onto the membrane surface through filtration deposition and the physical adhesion of PEI, resulting in weak adhesion between the particles and the membrane substrate. These particles are easily detached under high shear stress or backwashing conditions. Furthermore, the modified membrane in this method lacks photocatalytic self-cleaning capability, and flux recovery after fouling still requires external chemical cleaning.

[0006] Therefore, it is still necessary to develop a novel polyvinylidene fluoride membrane that integrates antibiotic separation and photocatalytic surface self-cleaning to achieve simultaneous separation and degradation of antibiotic pollutants, thereby alleviating membrane fouling and improving treatment efficiency. Summary of the Invention

[0007] The purpose of this invention is to overcome the shortcomings of the existing technology, which makes it difficult to simultaneously achieve antibiotic separation and photocatalytic surface self-cleaning, and to provide a modified polyvinylidene fluoride membrane, its preparation method, and its application.

[0008] The objective of this invention can be achieved through the following technical solutions: The first aspect of this invention provides a method for preparing a modified polyvinylidene fluoride (PVDF) membrane, the method comprising the following steps: S1: Bismuth source and sulfur source are dissolved in the first solvent and mixed, and bismuth sulfide particles are obtained by hydrothermal reaction; S2: The bismuth sulfide particles obtained in S1 are mixed with zirconium source, 2-aminoterephthalic acid and regulator in a second solvent and then subjected to hydrothermal reaction to obtain bismuth sulfide modified NH2-UIO-66 particles. S3: The polyvinylidene fluoride membrane is pretreated by immersing it in an alkaline solution to obtain a pretreated polyvinylidene fluoride membrane. S4: Pour a mixture containing acrylic acid, ethylene glycol and initiator onto the surface of the pretreated polyvinylidene fluoride membrane and heat it to obtain a polyacrylic acid-grafted polyvinylidene fluoride membrane. S5: Bismuth sulfide modified NH2-UIO-66 particles are dispersed in an aqueous phase, and then the dispersion is transferred to the surface of a polyvinylidene fluoride membrane grafted with polyacrylic acid to finally obtain the modified polyvinylidene fluoride membrane.

[0009] Further, in step S1, the bismuth source is any one or a combination of bismuth nitrate, bismuth chloride, bismuth sulfate, bismuth hydroxide, bismuth acetate, and bismuth phosphate, preferably bismuth nitrate.

[0010] Further, in step S1, the sulfur source is any one or a combination of sodium sulfide, potassium sulfide, sodium sulfate, ammonium sulfate, sulfur, and hydrogen sulfide, preferably sodium sulfide.

[0011] Further, in step S1, the molar ratio of the bismuth source to the sulfur source is (0.1~10):(0.1~10), preferably (1~5):(1.5~7.5).

[0012] Further, in step S1, the first solvent is any one or a combination of water, ethylene glycol, ethanol, and isopropanol, preferably ethylene glycol.

[0013] Furthermore, in step S1, the temperature of the hydrothermal reaction is 100-180 ℃.

[0014] Furthermore, in step S1, the hydrothermal reaction time is 3-36 h, preferably 3-12 h.

[0015] Further, in step S2, the mass ratio of the bismuth sulfide particles, zirconium source, and 2-aminoterephthalic acid is (0.1~2):(0.1~2):(0.1~3), preferably (0.8~1.5):(0.8~1.5):(1~2).

[0016] Further, in step S2, the zirconium source is any one or a combination of zirconium tetrachloride, zirconium oxychloride, zirconium n-propoxide, and zirconium nitrate, preferably zirconium tetrachloride.

[0017] Further, in step S2, the regulator is any one or a combination of formic acid, acetic acid, benzoic acid, and hydrochloric acid, preferably acetic acid.

[0018] Further, in step S2, the second solvent is any one or a combination of N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, and dimethyl sulfoxide, preferably N,N-dimethylformamide.

[0019] Furthermore, in step S2, the temperature of the hydrothermal reaction is 100-160 ℃.

[0020] Furthermore, in step S2, the hydrothermal reaction time is 12-36 h.

[0021] Further, in step S3, the alkali in the alkaline solution is any one or a combination of sodium hydroxide, potassium hydroxide, ammonia, sodium bicarbonate, potassium bicarbonate, sodium carbonate, and calcium hydroxide.

[0022] Further, in step S3, the concentration of alkali in the alkaline solution is 0.1-5 mol / L, preferably 1-5 mol / L.

[0023] Furthermore, in step S3, the temperature of the alkaline solution is 25-80 ℃, preferably 25-60 ℃.

[0024] Further, in step S3, the soaking time is 0.1-36 h, preferably 0.1-12 h.

[0025] Further, in step S4, the mass percentages of acrylic acid, ethylene glycol, and initiator in the mixture are 5-30 wt%, 0.5-5 wt%, and 0.5-1.5 wt%, respectively, preferably 8-26 wt%, 2-4 wt%, and 0.5-1.5 wt%.

[0026] Further, in step S4, the initiator is any one or a combination of sodium persulfate, ammonium persulfate, and potassium persulfate, preferably potassium persulfate.

[0027] Furthermore, in step S4, the heating temperature is 40-80 ℃.

[0028] Furthermore, in step S4, the heating time is 0.2-1.5 h.

[0029] Further, in step S4, the PVDF membrane is fixed to the surface of the circular steel hoop, the mixture is poured evenly onto the surface of the PVDF membrane, sealed, and then transferred to a heating device for constant heating at 50-70 ℃ for 30-60 min.

[0030] Further, in step S5, the particle concentration in the dispersion is 0.2-4 mg / mL, preferably 0.4-2 mg / mL.

[0031] Further, in step S5, the aqueous phase is a buffer solution with a pH of 4.0-8.0.

[0032] Further, in step S5, the bismuth sulfide-modified NH2-UIO-66 particles are ultrasonically dispersed in an aqueous phase for 30-60 min.

[0033] A second aspect of the present invention provides a modified polyvinylidene fluoride membrane, which is prepared by any of the above-described preparation methods.

[0034] A third aspect of this invention provides the application of a modified polyvinylidene fluoride membrane in the treatment of antibiotic wastewater.

[0035] Compared with the prior art, the present invention has the following technical advantages: (1) This invention innovatively introduces bismuth sulfide-modified NH2-UIO-66 particles onto a PAA-modified PVDF membrane, successfully preparing a modified polyvinylidene fluoride membrane integrating antibiotic separation and photocatalytic surface self-cleaning. The modified PVDF membrane prepared by this invention not only has excellent antibiotic retention performance but also good photocatalytic self-cleaning ability, with a water flux of up to 50 L·h. -1 ·m -2 ·bar -1 The single-dose ciprofloxacin rejection rate is >95%, and the water flux recovery rate is >60% under simulated sunlight irradiation, indicating significant application potential in antibiotic wastewater treatment.

[0036] (2) This invention innovatively employs a stepwise composite strategy of PVDF supporting substrate, PAA hydrophilic anchoring bridge, and Bi2S3 / NH2-UIO-66 functional particles. The PVDF membrane serves as the mechanical support substrate, ensuring the operational stability of the composite membrane in complex wastewater environments. Alkali pretreatment of the PVDF substrate combined with PAA grafting introduces a large number of carboxyl groups onto the membrane surface. This improves the hydrophilicity of the membrane surface and utilizes the chemical bonding between the carboxyl groups and the amino groups in NH2-UIO-66, as well as other forces, to achieve stable immobilization of Bi2S3 / NH2-UIO-66 particles, effectively solving the interfacial compatibility problem of easy detachment of inorganic particles in traditional blending modification. The introduction of Bi2S3 / NH2-UIO-66 composite particles not only utilizes the physical barrier effect of the particles to achieve efficient retention of antibiotic molecules but also endows the membrane with visible light response properties, enabling the membrane to achieve surface self-cleaning of retained pollutants under simulated sunlight irradiation. Through the synergistic effect of the above components, the membrane of the present invention simultaneously achieves multiple functional integrations, including high rejection rate (>95%) and photocatalytic self-cleaning (flux recovery rate >50%).

[0037] (3) The preparation of the Bi2S3 / NH2-UIO-66 modified PVDF membrane of the present invention is simple and easy to carry out, with a short process cycle, low cost, and good production process stability, making it suitable for large-scale industrial preparation.

[0038] (4) The modified polyvinylidene fluoride membrane prepared by this invention has good hydrophilicity and antifouling properties. The contact angle measured in air is 37°, which makes it difficult for oil droplets to adhere to the membrane surface, thereby improving the separation efficiency of oil-water emulsions to over 95%. Therefore, this membrane has significant application potential in antibiotic wastewater treatment. It can not only effectively separate antibiotics, but also achieve self-cleaning of the membrane surface and can be reused, providing a highly efficient and stable new solution for antibiotic separation technology. Attached Figure Description

[0039] Figure 1This is a SEM image of Bi2S3 / NH2-UIO-66 obtained in Example 1 of the present invention.

[0040] Figure 2 The above are flux bar charts for Embodiments 1-4 and Comparative Example 1 of the present invention.

[0041] Figure 3 The bar chart shows the rejection rates of Examples 1-4 and Comparative Example 1 of this invention.

[0042] Figure 4 The bar chart shows the flux recovery rates of Examples 1-4 and Comparative Example 1 of this invention. Detailed Implementation

[0043] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.

[0044] Unless otherwise specified, the reagents, methods, instruments, and equipment used in this invention are conventional in the art. Unless otherwise specified, the reagents and materials used in the following examples are all commercially available.

[0045] This invention provides a modified polyvinylidene fluoride (PVDF) membrane that integrates antibiotic separation and photocatalytic surface self-cleaning. Specifically, the modified PVDF membrane of this invention comprises, from bottom to top: a porous PVDF base membrane as a mechanically supporting substrate; a polyacrylic acid (PAA) layer grafted onto the PVDF backbone through alkali pretreatment and free radical polymerization, wherein the PAA molecular chains are rich in carboxyl groups; and Bi2S3 / NH2-UIO-66 composite particles anchored to the surface of the PAA layer and the inner wall of the membrane pores through chemical bonding.

[0046] Among them, the PVDF-based membrane, with its excellent chemical stability and mechanical strength, ensures the structural integrity of the composite membrane during long-term operation in high-pressure and complex wastewater environments. Alkali pretreatment combined with the introduction of PAA grafting improves the membrane's hydrophilicity through a large number of carboxyl groups. Furthermore, the chemical bonding between the carboxyl groups and the amino groups in NH2-UIO-66 achieves stable immobilization of the composite particles, effectively solving the interfacial compatibility problem between inorganic particles and the organic substrate and preventing particle loss during operation. The Bi2S3 / NH2-UIO-66 composite particles, as the core functional component, utilize the physical barrier and adsorption effects of the particles to achieve efficient retention of antibiotic molecules, while also endowing the membrane with visible light responsiveness, enabling the membrane to achieve surface self-cleaning of retained pollutants under simulated sunlight irradiation.

[0047] In summary, this invention achieves complementary advantages of each component through the stepwise composite of PVDF supporting substrate, PAA hydrophilic anchoring bridge, and Bi2S3 / NH2-UIO-66 functional particles, enabling the modified membrane to have both high retention rate and photocatalytic self-cleaning performance. It can simultaneously achieve antibiotic separation and surface self-cleaning, making it suitable for long-term stable operation.

[0048] The modified polyvinylidene fluoride membrane of the present invention can be obtained by the following preparation method: S1. Bismuth nitrate pentahydrate (Co(NO3)2·6H2O) and sodium sulfide nonahydrate (Na2S·9H2O) were added sequentially to ethylene glycol (EG) and mixed. The mixture was stirred until homogeneous. Then, it was transferred to a high-pressure reactor lined with polytetrafluoroethylene for hydrothermal reaction. After centrifugation, the supernatant was removed, the lower precipitate was taken and vacuum dried to obtain bismuth sulfide (Bi2S3) particles.

[0049] S2. The Bi2S3 particles obtained in S1, zirconium tetrachloride (ZrCl4), 2-aminoterephthalic acid (H2ATA), and acetic acid (HAc) are sequentially added to N,N-dimethylformamide (DMF) and mixed. The mixture is stirred until homogeneous, and then transferred to a polytetrafluoroethylene-lined high-pressure reactor for hydrothermal reaction. After centrifugation, the supernatant is removed, the lower precipitate is taken and vacuum dried to obtain Bi2S3 / NH2-UIO-66 particles.

[0050] S3. The polyvinylidene fluoride (PVDF) membrane is pretreated by immersing it in a hot sodium hydroxide (NaOH) solution to obtain a sodium hydroxide-treated PVDF membrane.

[0051] S4. Acrylic acid (AA), ethylene glycol (EG), and potassium persulfate (KPS) are added to deionized water in sequence and mixed. The mixture is stirred until homogeneous. The mixture is then poured onto the surface of a sodium hydroxide PVDF membrane and heated to obtain a PAA-PVDF membrane.

[0052] S5. Disperse Bi2S3 / NH2-UIO-66 particles in a buffer solution with a pH of 4.0-8.0, and then transfer them to the surface of a PAA-PVDF membrane to obtain a modified PVDF membrane with Bi2S3 / NH2-UIO-66 grafted onto the surface.

[0053] Those skilled in the art can replace the bismuth source, sulfur source, zirconium source, base, initiator, regulator, and solvent, and select other existing compounds or formulations of the same type. Furthermore, those skilled in the art can adjust the proportions of each component and the reaction parameters according to the actual reaction conditions.

[0054] The following detailed description is based on specific embodiments.

[0055] Example 1: This embodiment provides a modified polyvinylidene fluoride membrane that integrates antibiotic separation and photocatalytic surface self-cleaning. The specific preparation method is as follows: S1. At room temperature, 4 mmol Bi(NO3)3·5H2O was added to 20 mL of EG solution (designated as solution A), and 6 mmol Na2S·9H2O was added to 20 mL of EG solution (designated as solution B). After sonication for 15 min, solution B was added to solution A and stirred for 30 min. The mixture was then transferred to a polytetrafluoroethylene-lined high-pressure reactor and kept at 180 ℃ for 3 h. After natural cooling to room temperature, the product was collected by centrifugation at 8000 rpm. The product was washed 3-4 times alternately with water and ethanol until the supernatant was clear. The product was then dried in a vacuum drying oven at 60 ℃ for 12 h to obtain Bi2S3 particles.

[0056] S2. Under room temperature conditions, 50 mg of Bi₂S₃ particles, 0.2334 g of ZrCl₄, and 0.1812 g of H₂ATA were weighed and dispersed sequentially in 60 mL of DMF. 5 mL of acetic acid was added, and the mixture was sonicated for 10 min and magnetically stirred for 50 min to ensure homogeneity. The mixture was then transferred to a polytetrafluoroethylene-lined high-pressure reactor and incubated at 120 °C for 12 h. After natural cooling to room temperature, the product was collected by centrifugation and washed alternately with DMF and methanol 3-4 times until the supernatant was clear. The mixture was then centrifuged at 8000 rpm and dried in a vacuum drying oven at 60 °C for 12 h to obtain Bi₂S₃ / NH₂-UIO-66 particles.

[0057] S3. Immerse the original PVDF membrane (pore size 0.45 μm) in a 2.5 mol / L sodium hydroxide solution and heat at 60 ℃ for 15 min. After alkali treatment, rinse and soak repeatedly with pure water to remove residual alkali.

[0058] S4. Fix the PVDF membrane in a ring-shaped steel hoop. Then, dissolve 8.83 g AA, 1.17 g EG, and 0.5 g KPS in 39.5 g deionized water, mix thoroughly, and slowly pour the mixture into the reaction ring to ensure full contact with the membrane surface. The reaction is carried out at 60 °C for 40 minutes. Finally, wash the resulting membrane with pure water and soak it in deionized water on a shaker for 24 hours to obtain PAA-PVDF.

[0059] S5. At room temperature, 4 mg of Bi2S3 / NH2-UIO-66 particles were dispersed in 5 ml of buffer (pH=5.5, MES buffer), and sonicated for 45 min under ice-water bath conditions to obtain a dispersion. The dispersion was then transferred to the surface of a PAA-PVDF membrane and reacted at room temperature for 24 h to obtain a modified PVDF membrane with Bi2S3 / NH2-UIO-66 grafted onto the surface, denoted as M1.

[0060] Example 2: This embodiment provides a modified polyvinylidene fluoride (PVDF) membrane that integrates antibiotic separation and photocatalytic surface self-cleaning. The difference from Example 1 is that in step S4 of this embodiment, 6.63 g of AA, 0.87 g of EG, and 0.5 g of KPS are dissolved in 42 g of deionized water. All other operations are the same as in Example 1. The final modified PVDF membrane with surface grafted Bi2S3 / NH2-UIO-66 is denoted as M2.

[0061] Example 3: This embodiment provides a modified polyvinylidene fluoride (PVDF) membrane that integrates antibiotic separation and photocatalytic surface self-cleaning. The difference from Example 1 is that in step S2 of this embodiment, 25 mg of Bi2S3 particles are weighed. All other operations are the same as in Example 1, and the final modified PVDF membrane with surface grafted Bi2S3 / NH2-UIO-66 is denoted as M3.

[0062] Example 4: This embodiment provides a modified polyvinylidene fluoride (PVDF) membrane that integrates antibiotic separation and photocatalytic surface self-cleaning. The difference from Example 1 is that in step S5 of this embodiment, 2 mg of Bi₂S₃ / NH₂-UIO-66 particles are dispersed in a buffer solution. All other operations are the same as in Example 1, and the final modified PVDF membrane with Bi₂S₃ / NH₂-UIO-66 grafted onto its surface is designated M4.

[0063] Comparative Example 1: This comparative example provides a modified polyvinylidene fluoride membrane that does not contain Bi2S3 / NH2-UIO-66 particles. The specific preparation method is as follows: S1. Immerse the original PVDF membrane in a 2.5 mol / L sodium hydroxide solution and heat at 60 °C for 15 min. After alkali treatment, rinse and soak repeatedly with pure water to remove residual alkali.

[0064] S2. Fix the membrane in a ring-shaped steel hoop, then dissolve 8.83 g AA, 1.17 g EG, and 0.5 g KPS in 39.5 g deionized water, mix thoroughly, and slowly pour the mixture into the reaction ring to ensure full contact with the membrane surface. The reaction is carried out at 60 °C for 40 minutes. Finally, wash the resulting membrane with pure water and soak it in deionized water on a shaker for 24 hours to obtain PAA-PVDF, denoted as M0.

[0065] Based on the modified polyvinylidene fluoride membranes containing Bi2S3 / NH2-UIO-66 particles prepared in Examples 1-4 above and the modified polyvinylidene fluoride membrane containing Bi2S3 / NH2-UIO-66 particles in Comparative Example 1, this invention further studies the permeation and retention performance of the modified PVDF membranes using pressurized membrane separation technology.

[0066] Under certain pressure, small-molecule solutes and solvents will pass through a membrane with a specific pore size, while large-molecule solutes will not pass through and will be retained. Specific tests are as follows: The photocatalytic self-cleaning ability of the modified PVDF membrane was studied using simulated solar irradiation. The flux recovery rate of the modified PVDF membrane before and after irradiation was used to represent the effect of retaining the target antibiotic solution. Ciprofloxacin and deionized iron were blended, ultrasonically dispersed at room temperature for 30 min, and stirred for 20 min to obtain a stable simulated solution of the target antibiotic contamination at a concentration of 20 mg / L.

[0067] A typical experimental procedure is: flux test, interception test, and flux test after illumination.

[0068] (1) Water flux measurement: The modified PVDF membrane was pre-pressurized with pure water for 30 minutes to eliminate initial flux fluctuations, and then the change in permeate volume over time was recorded.

[0069] (2) Contaminant solution retention test: A specific volume of 30 mL of ciprofloxacin solution was poured into a vacuum filter, the filtrate was collected, and the concentration of residual CIP in the filtered solution was determined by the absorbance at 278 nm using a UV-Vis spectrophotometer.

[0070] (3) Flux test after light exposure: The modified PVDF membrane after filtration was immersed in 50 mL of deionized water and placed under a daylight simulation lamp (ULTRA VITALUX 300 W 230 V E27) for 1 hour. After a simple water wash, the water flux was tested, the water flux was recorded, and the flux recovery rate was calculated.

[0071] Flux and retention tests were conducted at an effective membrane area of ​​0.00132025 cm². 2 The test was conducted on a vacuum filtration system with a pressure of 1 bar. The water flux J of the modified PVDF membrane was measured. w The retention rate R, flux recovery rate, total contamination rate, reversible contamination rate, and irreversible contamination rate can be calculated by formulas (1) to (6), respectively.

[0072] (1).

[0073] Among them, J w Expressed as liquid flux (L·h) -1 ·m-2 ·bar -1 V represents the permeate volume of pure water (L), and A represents the effective membrane area (m²). 2 ), where t represents the infiltration time (h) and ΔP represents the operating pressure (bar).

[0074] (2).

[0075] Where R is the separation efficiency (%), C perm and C feed These represent the concentrations (mg / L) of contaminants in the permeate and feed liquid, respectively.

[0076] (3).

[0077] (4).

[0078] (5).

[0079] (1).

[0080] Where FRR (%) represents flux recovery rate, R t (%) represents the total pollution rate, R r (%) represents the rate of irreversible pollution, R i (%) represents the reversible contamination rate. J1 is the initial water flux, J2 is the ciprofloxacin permeation flux, and J3 is the water flux after light-washing.

[0081] The results of flux testing, interception testing, and post-illumination flux testing are shown in Table 1. See the bar chart for details. Figures 2-4 .

[0082] Table 1 Summary of flux test, interception test, and post-illumination flux test results Figure 1 This is a scanning electron microscope (SEM) image (scale bar 10 μm) of the surface of the PVDF film modified with Bi2S3 / NH2-UIO-66 grafted onto the surface, prepared in Example 1 of this invention. Figure 1It can be clearly observed that a large number of particulate materials are uniformly distributed on the surface of the modified PVDF membrane, without completely obscuring the membrane pores. These particles are well dispersed on the PAA graft layer, without obvious self-aggregation or local stacking, indicating that the particles maintain good dispersion stability during loading. Further observation revealed that these particles are not simply scattered or physically accumulated on the membrane surface, but are tightly bound to the membrane surface and grow along the edges of the membrane pores. In addition, most of the pore structure on the membrane surface remains open, without being excessively covered or blocked by particles, indicating that the particle loading design of this invention is reasonable, ensuring a sufficient number of photocatalytic and adsorption active sites while avoiding membrane pore blockage and water flux reduction due to excessive loading.

[0083] Water flux and rejection rate are two core indicators for evaluating membrane separation performance, and there is often a trade-off between them. (See Table 1 and...) Figure 2 , Figure 3 As shown, the comprehensive influence of material design variables on separation performance can be clearly observed from the comparison of data in each group. Specifically, the comparison between Examples 1 and 2 shows that a reduction in PAA grafting amount leads to an insufficient number of carboxyl anchoring sites on the membrane surface, which in turn reduces the loading of Bi2S3 / NH2-UIO-6 particles subsequently anchored through coordination. The reduction in particle loading amount lowers the resistance to water transfer on the membrane surface (increases flux), but at the same time, the adsorption, enrichment, and sieving effects of the MOF on antibiotics are weakened (retention rate decreases significantly). This comparison indicates that the PAA grafting amount must reach a sufficient level to ensure the effective loading and retention performance of the MOF. The PAA grafting amount in Example 1 is a necessary condition to ensure a retention rate >95% in this system.

[0084] A comparison of Examples 1 and 4 shows that, due to the halving of the particle dispersion concentration in Example 4, the absolute amount of Bi₂S₃ / NH₂-UIO-66 particles actually anchored on the membrane surface decreased. Its retention rate decreased from 95.62% in Example 1 to 93.88%, still maintaining a relatively high level; however, its water flux decreased from 45 L·h⁻¹. -1 ·m -2 ·bar -1 Significantly reduced to 35 L·h -1 ·m -2 ·bar -1 This may be attributed to the preferential distribution of sparsely grafted particles at the pore inlet or inner wall region, which creates a significant obstruction effect on the water transport path. As the particle loading increases, a uniform and dense grafted layer gradually forms. Figure 1 The diffusion and permeation efficiency of water molecules on the membrane surface were significantly improved. This comparison shows that there is an optimal range for particle concentration; too low a concentration not only fails to improve flux but also leads to decreased permeability due to uneven distribution.

[0085] As can be seen from the comparison between Example 1 and Comparative Example 1, the introduction of Bi2S3 / NH2-UIO-66 particles increased the water flux of Example 1 (45 L·h) -1 ·m -2 ·bar -1 Both the rejection rate (95.62%) and the retention rate were higher than those of Comparative Example 1. This result fully demonstrates that a suitable and uniformly loaded Bi2S3 / NH2-UIO-66 particles can simultaneously improve the retention rate without increasing or even decreasing the water transfer resistance. The improvement in water flux brought about by particle loading can be attributed to the enhancement of the polar microenvironment on the membrane surface. The carboxyl groups of PAA and the polar groups such as Zr-OH, Bi-OH, and -NH2 on the particle surface work synergistically to form more hydrogen bonds with water molecules, constructing a hydration layer that is conducive to the preferential permeation of water molecules.

[0086] A comparison of Examples 1-4 with Comparative Example 1 shows that Example 1 achieved the optimal balance between water flux and retention rate under the combined conditions of PAA grafting amount and particle loading concentration. This proves that the material design strategy of the present invention successfully broke the traditional trade-off between flux and retention rate, and achieved simultaneous improvement of both.

[0087] Furthermore, flux recovery rate (FRR) is a core indicator for evaluating membrane self-cleaning ability. As shown in Table 1, the FRR of Examples 1-4 were all significantly higher than that of Comparative Example 1. The FRR of Example 1 was 33.32 percentage points higher than that of Comparative Example 1, demonstrating that the photocatalytic activity of Bi2S3 / NH2-UIO-6 is the fundamental reason for the improved self-cleaning performance, namely, the mineralization and degradation of antibiotics attached to the membrane surface to effectively remove the fouling layer. Comparative Example 1 lacked photocatalytic functional groups and could only rely on water washing for desorption, resulting in a significantly lower FRR. These results indicate that an appropriate loading of Bi2S3 / NH2-UIO-6 is key to fully realizing the photocatalytic self-cleaning effect, and Example 1 achieved the best self-cleaning performance in this series.

[0088] Based on the above performance evaluations, this invention successfully achieves multifunctional integration of modified PVDF membranes through a stepwise composite strategy involving a PVDF supporting substrate, a PAA hydrophilic anchoring bridge, and Bi2S3 / NH2-UIO-66 functional particles. The PAA layer not only imparts the retention performance of the composite membrane base but also solves the interfacial compatibility problem between inorganic particles and the organic substrate. Bi2S3 / NH2-UIO-66 endows the membrane with photoresponsive self-cleaning capabilities. The synergistic effect of these three elements enables the composite membrane to possess both highly efficient antibiotic retention and excellent anti-fouling and regeneration capabilities. In summary, the modified polyvinylidene fluoride membrane of this invention achieves highly efficient antibiotic retention while also possessing a certain degree of photocatalytic self-cleaning ability, providing a feasible technical path for the development of integrated membrane materials that combine retention, degradation, and self-cleaning, and showing promising application prospects in the field of antibiotic wastewater treatment.

[0089] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.

Claims

1. A method for preparing a modified polyvinylidene fluoride membrane, characterized in that, The preparation method includes the following steps: S1: Bismuth source and sulfur source are dissolved in the first solvent and mixed, and bismuth sulfide particles are obtained by hydrothermal reaction; S2: The bismuth sulfide particles obtained in S1 are mixed with zirconium source, 2-aminoterephthalic acid and regulator in a second solvent and then subjected to hydrothermal reaction to obtain bismuth sulfide modified NH2-UIO-66 particles. S3: The polyvinylidene fluoride membrane is pretreated by immersing it in an alkaline solution to obtain a pretreated polyvinylidene fluoride membrane. S4: Pour a mixture containing acrylic acid, ethylene glycol and initiator onto the surface of the pretreated polyvinylidene fluoride membrane and heat it to obtain a polyacrylic acid-grafted polyvinylidene fluoride membrane. S5: Bismuth sulfide modified NH2-UIO-66 particles are dispersed in an aqueous phase, and then the dispersion is transferred to the surface of a polyvinylidene fluoride membrane grafted with polyacrylic acid to finally obtain the modified polyvinylidene fluoride membrane.

2. The method for preparing a modified polyvinylidene fluoride membrane according to claim 1, characterized in that, In step S1, the bismuth source is any one or a combination of bismuth nitrate, bismuth chloride, bismuth sulfate, bismuth hydroxide, bismuth acetate, and bismuth phosphate. The sulfur source is any one or a combination of sodium sulfide, potassium sulfide, sodium sulfate, ammonium sulfate, sulfur, and hydrogen sulfide; The molar ratio of the bismuth source to the sulfur source is (0.1~10):(0.1~10). The first solvent is any one or a combination of water, ethylene glycol, ethanol, and isopropanol.

3. The method for preparing a modified polyvinylidene fluoride membrane according to claim 1, characterized in that, In step S1, the temperature of the hydrothermal reaction is 100-180 ℃, and the time of the hydrothermal reaction is 3-36 h.

4. The method for preparing a modified polyvinylidene fluoride membrane according to claim 1, characterized in that, In step S2, the mass ratio of the bismuth sulfide particles, zirconium source, and 2-aminoterephthalic acid is (0.1~2):(0.1~2):(0.1~3). The zirconium source is any one or a combination of zirconium tetrachloride, zirconium oxychloride, zirconium n-propoxide, and zirconium nitrate. The regulator is any one or a combination of formic acid, acetic acid, benzoic acid, and hydrochloric acid; The second solvent is any one or a combination of N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, and dimethyl sulfoxide; The hydrothermal reaction temperature is 100-160 ℃, and the hydrothermal reaction time is 12-36 h.

5. The method for preparing a modified polyvinylidene fluoride membrane according to claim 1, characterized in that, In step S3, the alkali in the alkaline solution is any one or a combination of sodium hydroxide, potassium hydroxide, ammonia, sodium bicarbonate, potassium bicarbonate, sodium carbonate, and calcium hydroxide. The concentration of alkali in the alkaline solution is 0.1-5 mol / L, and the temperature of the alkaline solution is 25-80 ℃; The soaking time is 0.1-36 h.

6. The method for preparing a modified polyvinylidene fluoride membrane according to claim 1, characterized in that, In step S4, the mass percentages of acrylic acid, ethylene glycol, and initiator in the mixture are 5-30 wt%, 0.5-5 wt%, and 0.5-1.5 wt%, respectively. The initiator is any one or a combination of sodium persulfate, ammonium persulfate, and potassium persulfate; The heating temperature is 40-80 ℃, and the heating time is 0.2-1.5 h.

7. The method for preparing a modified polyvinylidene fluoride membrane according to claim 1, characterized in that, In step S4, the PVDF membrane is fixed to the surface of the circular steel hoop, the mixture is poured evenly onto the surface of the PVDF membrane, sealed, and then transferred to a heating device for constant heating at 50-70 ℃ for 30-60 min.

8. The method for preparing a modified polyvinylidene fluoride membrane according to claim 1, characterized in that, In step S5, the particle concentration in the dispersion is 0.2-4 mg / mL; The aqueous phase is a buffer solution with a pH of 4.0-8.

0.

9. A modified polyvinylidene fluoride membrane, characterized in that, It is prepared by the preparation method according to any one of claims 1-8.

10. The application of the modified polyvinylidene fluoride membrane according to claim 9 in the treatment of antibiotic wastewater.

Citation Information

Patent Citations

  • Preparation method, product and application of hydrophilic zirconium-based MOF doped PVDF film

    CN112090300A